Using Meta-analyses to Generate Alternative Prediction Equations for the Space Requirements of Finishing Pigs - J. R. Flohr; M. D. Tokach; S. S. Dritz; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2015)
Data from existing literature examining the influence of floor space allowance on the growth of finishing pigs were used to develop prediction equations for ADG, ADFI, and G:F. Two sets of databases were used. The first database included information from studies examining the influence of floor space allowance. The second database included the aforementioned literature, along with papers examining the impact of floor space after pigs were removed from the pen (topping). The first database included 27, 25, and 25 papers for ADG, ADFI, and G:F, respectively. The second database included 30, 28, and 28 papers for ADG, ADFI, and G:F, respectively. The predictor variables tested were floor space (m2/pig),k(floor space, m2/final BW, kg0.67), initial BW (kg), final BW (kg), feeder space (pigs per feeder hole), water space (pigs per waterer), group size (pigs per pen), gender, floor type, and study length (d). A mixed linear model approach was used for model development, and floor space treatments within each experiment were the experimental units. Evaluations of models with significant terms were conducted using the Bayesian Information Criterion (BIC). The optimum equations to predict finishing ADG, ADFI, and G:F for the first database were: ADG, g =395.57+(15,727 ×k)-(221,705 ×k2)-(3.6478 × Initial BW, kg)+ (2.209 × Final BW, kg)+(67.6294 ×k× Initial BW, kg) ADFI, g =802.07+(20,121×k)-(301,210 ×k2)-(1.5985 × Initial BW, kg)+ (11.8907 × Final BW, kg )+(159.79 ×k× Initial BW, kg) G:F =Predicted ADG/Predicted ADFI The optimum equations to predict ADG, ADFI, and G:F for the second database were: ADG, g =337.57+(16,468 ×k)-(237,350 ×k2)-(3.1209 × Initial BW, kg)+ (2.569 × Final BW, kg)+(71.6918 ×k× Initial BW, kg) ADFI, g = 833.41+(24,785 × k)-(388,998 ×k2)-(3.0027 × Initial BW, kg)+ (11.246 × Final BW, kg)+(187.61 ×k× Initial BW, kg) G:F =Predicted ADG/Predicted ADFI All multi-term models reduced the BIC values compared to individual term models. Data from 3 separate experiments examining the effects of floor space allowance on growth performance were used to evaluate the accuracy of the prediction equations herein and also previously developed prediction equations (Kornegay and Notter, 1984; Powell et al., 1993; and Gonyou et al., 2006). Predicted values from equations reported herein improved model evaluation statistics compared to Kornegay and Notter (1984), and Powell (1993), and were comparable to predicted values by Gonyou et al. (2006), with improved root mean square error calculations that suggest more accurate predictions of growth rate. Between the equations developed from the databases, those from the second database more accurately predict growth performance at heavier BW ranges as well as the growth performance of finishing pigs remaining in a pen after pigs are removed.
Keywords: finishing pig; floor space; prediction equation